Security Issues of Routing Protocols in MANETs - Gandhi, Kaushal; Narula, Rajneesh; Khullar, Sumeer; Arora, Anish (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
There are a number of routing protocols developed by researchers. Due to the nature of ad hoc networks, secure routing is an important area of research in developing secure routing protocols. Although researchers have proposed several secure routing protocols, their resistance towards various types of security attacks and efficiency are primary points of concern in implementing these protocols. This paper presents some of the available secure routing protocols and most common attack patterns against ad hoc networks. Routing protocols are subjected to case studies against the most commonly identified attack patterns such as: denial-of-service attack, tunneling, spoofing, black hole attack and wormhole attack etc. In MANET, the nodes also function as routers that discover and maintain routes to other nodes in the network. Establishing an optimal and efficient route between the communicating parties is the primary concern of the routing protocols of MANET. Any attack in routing phase may disrupt the overall communication and the entire network can be paralyzed. Thus, security in network layer plays an important role in the security of the whole network. A number of attacks in network layer have been identified and studied in security research. An attacker can absorb network traffic, inject themselves into the path between the source and destination and thus control the network traffic flow.